Time-specific effects of perinatal glucocorticoid treatment on anterior pituitary morphology, annexin 1 expression and adrenocorticotrophic hormone secretion in the adult female rat. - John, C; Theogaraj, E; Christian, H; Morris, J; Smith, S; Buckingham, J (2006)
Perinatal glucocorticoid (GC) treatment is increasingly associated with long-term disturbances in hypothalamo-pituitary-adrenocortical function. In the male rat, such treatment induces profound molecular, morphological and functional changes in the anterior pituitary gland at adulthood. To determine whether these effects are sex-specific, we have examined the effects of perinatal dexamethasone treatment on the female pituitary gland, focusing on (i) the integrity of the annexin 1 (ANXA1) dependent regulatory effects of GCs on adrenocorticotrophic hormone (ACTH) release and (ii) corticotroph and folliculo-stellate (FS) cell morphology. Dexamethasone was given to pregnant (gestational days 16-19) or lactating (days 1-7 post partum) rats via the drinking water (1 microg/ml); controls received normal drinking water. Pituitary tissue from the female offspring was examined ex vivo at adulthood (60-90 days). Both treatment regimes reduced the intracellular and cell surface ANXA1 expression, as determined by western blot analysis and quantitative immunogold electron microscopic histochemistry. In addition, they compromised the ability of dexamethasone to suppress the evoked release of ACTH from the excised tissue in vitro, a process which requires the translocation of ANXA1 from the cytoplasm to the cell surface of FS cells. Although neither treatment regime affected the number of FS cells or corticotrophs, both altered the subcellular morphology of these cells. Thus, prenatal dexamethasone treatment increased while neonatal treatment decreased FS cell size and cytoplasmic area. By contrast, corticotroph size was unaffected by either treatment, as also was the size of the secretory granules. Corticotroph granule density and margination were, however, increased markedly by the prenatal treatment, while the neonatal treatment had no effect on granule density but decreased granule margination. Thus, perinatal dexamethasone treatment exerts long-term effects on the female pituitary gland, altering gene expression, cell morphology and the ANXA1-dependent GC regulation of ACTH secretion. The changes are similar but not identical to those reported in the male.